Contralateral Axillary Lymph Node Metastasis of Breast Cancer: Retrospective Analysis and Literature Review - Zhang, Liang; Wang, Xin zhao; Li, Chao; Yu, Qian; Liu, Zhaoyun; Yu, Zhi yong (Frontiers in Oncology, 2022)
Background Contralateral axillary lymph node metastasis (CAM) is classified as distant metastasis in guidelines, but the prognosis is better than that of stage IV patients. It is controversial to classify CAM as a distant metastasis or a regional metastasis, and the optimal treatment strategy for CAM is unknown. Patients and Methods Breast cancer patients who were confirmed by pathology and treated at Shandong Cancer Hospital between January 2012 and July 2021 were included in our study. We retrospectively reviewed the medical records of the patients for their clinical features, pathological diagnosis, treatment strategy, and follow-up data. Survival analysis was calculated by Kaplan–Meier analysis, and patient matching was performed by case–control matching. Results A total of 60 patients were included, and there were 49 metachronous CAM cases and 11 synchronous CAM cases. The prognosis of isolated CAM patients was better than that of patients with other distant metastases in terms of CAM-OS and PFS with significant differences (median CAM-OS 71.0 vs. 30.0 months, P=0.022; median PFS 42.0 vs. 11.0 months, P=0.009) and OS without significant differences (median OS 126.0 vs. 79.0 months, P=0.111). The five-year survival rate of isolated CAM patients was 67.4%, and the five-year disease-free survival (DFS) rate was 52.9%. The prognosis of CAM patients was similar to that of N3M0 patients in terms of OS (mean OS 82.4 vs. 65.6 months, P=0.537) and DFS (mean PFS 54.5 vs. 52.6 months, P=0.888). Axillary lymph node dissection (ALND) or low-middle level ALND significantly improved the OS (mean OS 237.4 vs. 111.0 months, P=0.011), CAM-OS (mean CAM-OS 105.2 vs. 46.6 months, P = 0.002), and PFS (mean PFS 92.3 vs. 26.9 months, P = 0.001) of isolated CAM patients. Axillary radiotherapy improved PFS, CAM-OS, and OS but without significant differences (mean PFS 80.0 vs. 46.6 months, P = 0.345; mean CAM-OS 86.8 vs. 72.1 months, P = 0.338; mean OS 147.6 vs. 133.0 months, P = 0.426). Conclusion CAM should be diagnosed as local recurrence and treated with aggressive and curative rather than palliative strategies. Contralateral axillary surgery and radiotherapy are recommended for isolated CAM patients.